The Relationship of Knowledge about Patient Care with Family Anxiety Levels in Intensive Care Unit of Antonius Pontianak Hospital - Kristina Afrida Herlita; Ira Octavi Siagian; Juliyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the intensive care unit of Santo Antonius Hospital Pontianak with p value = 0.00 Family members will experience anxiety when facing one of the family members who is admitted to the ICU. Anxiety in the family can interfere with the patient's treatment process, because anxiety can cause stress in the family that can affect treatment support. Method: This study is a quantitative research that uses a correlative descriptive design with a cross sectional design. Sampling sampling technique with Total Sampling of 41 people. Croncbach's Alpha validity test result of 0.901 and proven reliable with > result of 0.6 Result: Most of the respondents (56.1%) had good knowledge about treatment in the ICU of St. Antonius Hospital Pontianak. Almost half of the respondents (36.6%) experienced mild anxiety because their families were treated at St. Anthony's Hospital. The results of statistical tests using Chi Square and the level of significance (α) 0.05 were obtained There is a relationship between knowledge about patient care and the level of family anxiety in the intensive care unit room of St. Antonius Hospital Pontianak with a p value = 0.001. Conclusion: There is a relationship between knowledge about patient care and the level of family anxiety.